2014
DOI: 10.1117/12.2063657
|View full text |Cite
|
Sign up to set email alerts
|

Source coding for transmission of reconstructed dynamic geometry: a rate-distortion-complexity analysis of different approaches

Abstract: Live 3D reconstruction of a human as a 3D mesh with commodity electronics is becoming a reality. Immersive applications (i.e. cloud gaming, tele-presence) benefit from effective transmission of such content over a bandwidth limited link. In this paper we outline different approaches for compressing live reconstructed mesh geometry based on distributing mesh reconstruction functions between sender and receiver. We evaluate rate-performance-complexity of different configurations. First, we investigate 3D mesh co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Following several experiments and evaluations of techniques available for immersive media applications, it was found that point clouds were particularly suitable for these kinds of applications. Point cloud data scored well in experiments comparing visual quality, bitrate, and compression performance as well as computational complexity [38]. In addition, other use cases were introduced such as free viewpoint broadcasting and 3D scans produced by mobile mapping systems.…”
Section: A Cfp Developmentmentioning
confidence: 95%
“…Following several experiments and evaluations of techniques available for immersive media applications, it was found that point clouds were particularly suitable for these kinds of applications. Point cloud data scored well in experiments comparing visual quality, bitrate, and compression performance as well as computational complexity [38]. In addition, other use cases were introduced such as free viewpoint broadcasting and 3D scans produced by mobile mapping systems.…”
Section: A Cfp Developmentmentioning
confidence: 95%